Realizing Fiscal Justice: A Juridical and Empirical Analysis of Boarding House and Hospitality Taxation in the Post-HKPD Local Regulatory Framework - Agus Riartono; Mastur (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The reform of regional taxation through Law Number 1 of 2022 on Fiscal Relations between the Central Government and Regional Governments (HKPD) has transformed the Hotel Tax regime into the Certain Goods and Services Tax (PBJT) on Hospitality Services. This regulatory change has generated both juridical and empirical challenges, particularly concerning boarding houses (indekost), which share several characteristics with hotel businesses but differ significantly in terms of economic capacity and operational scale. This study aims to examine the juridical construction of boarding house and hotel taxation in the post-HKPD era, analyze its implementation in Semarang Regency, and evaluate its conformity with the principles of fiscal justice. The research employs a normative-empirical (socio-legal) approach using statutory, conceptual, and empirical methods through regulatory analysis, observation, and document review. The findings indicate that regulatory harmonization has been achieved normatively through the implementation of PBJT on Hospitality Services; however, practical implementation continues to face challenges related to taxpayer registration, compliance, and supervision. Fiscal justice analysis reveals that differences in economic capacity between boarding house businesses and hotels have not been fully accommodated within the existing tax framework. This study recommends regulatory harmonization among local governments, the digitalization of tax administration, and the adoption of tax policies that more adequately reflect taxpayers’ economic capacity in order to promote greater fiscal justice.